A study of deep neck spaces infection in present era at tertiary care teaching hospital - Khavdu, Paresh J.; Fefar, Alpesh D.; Mistry, Sejal N.; Chavada, Payal S. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Deep neck spaces infection is a common challenging condition for otolaryngologist in day to day practice even after availability of higher antibiotics. It may leads to considerable morbidity and complications. The aim of the study was to find out prevalence, predisposing factors and changing trend of deep neck spaces infection in this broad spectrum antibiotics era. Methods: This prospective study was carried out at P.D.U. Medical College and Hospital, Rajkot. 120 Patients were studied who came with deep neck space infection. Results: In this study majority of patient were in the age group of 41-60 year. Odontogenic and oropharyngeal infectionare the most common etiologies. Staphylococcus aureus, Streptococcus, E. colli, Klebsiella and anaerobes were the microorganisms commonly isolated in pus culture and sensitivity test. Conclusions: In spite of availability of broad spectrum antibiotics in present day deep neck spaces infection is the most commonly noticeable condition in developing countries and may lead to considerable morbidity and complications. Inadequate nutritional status, poor oral hygiene and lack of awareness in dental health are common predisposing factors for deep neck spaces infection.